(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Transcatheter aortic valve implantation has become the treatment of choice for high-risk patients with symptomatic aortic stenosis. In vitro investigation of the hydrodynamic performance of valve prostheses (TAVP) is necessary to predict the expected clinical performance. Opening and closing of TAVP are influenced by complex vortices inside the aortic root (AR) distal the TAVP. Technical models of the AR must be used to obtain reliable data in an in vitro testing environment. The current study presents the 3D-reconstruction and -printing of a technical model of the AR based on a human AR for the hydrodynamic in vitro testing of TAVP.